Analysis of the competitiveness and commercialization of the Mexican pecan nut in the international market - Ávila Arce, Adanelly; Gonzalez Milan, David; Montaño Mendez, Iliana Enriqueta; Vizcaíno Villareal, Luis Alberto (Revista Mexicana de Ciencias Agrícolas, 2020)
The production, process and industrialization of the Mexican walnut are a topic of great importance for the economy and development of the country (particularly for the producing states), as well as the commercialization and behavior of the market, local and international. Given the above, the main objective of this document is to analyze various aspects of the pecan nut (hereinafter it will be referred to with the generic term: walnut) in the international market, such as competitiveness, production and marketing. Using data from the Food and Agriculture Organization of the United Nations (FAO), the Agri-Food and Fisheries Information Service (SIAP), the United States Department of Agriculture (USDA) and the National Institute of Statistics and Geography (INEGI), relevant results were obtained where it was identified that the largest buyers and trading partners of this product are Mexico, the United States of America and China, the latter being the main competitor of pecan nuts in the international market, despite the fact that Mexico's competitiveness It has increased in recent years.
Keywords: competitiveness; production; walnut